2022
DOI: 10.32920/ihtp.v2i1.1590
|View full text |Cite
|
Sign up to set email alerts
|

(Im)mobilities and life satisfaction in times of COVID-19: The case of older persons in Switzerland

Abstract: The COVID-19 pandemic led to changes in mobilities worldwide. Physical movement and social contact are shown to be correlated to life satisfaction. In this paper we are interested in how during the pandemic other types of mobilities relate to life satisfaction. The paper draws on a survey (N=643) among persons aged 65+ in Switzerland. Results show that engagement in communicative mobilities are related to higher life satisfaction, imaginative mobilities only partially relate to life satisfaction, and virtual m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…Moreover, Italian natives relied on telephone communication as a coping mechanism more than the other two groups. While staying in touch with family and friends through phone and other media use has been correlated with life satisfaction during the first semi-lockdown in Switzerland (Dones et al, 2022 ), studies found that non-personal communication does not substitute face-to-face interactions and it is not a protective strategy against loneliness among older adults (Pan et al, 2021 ; König and Isengard, 2023 ). Further research should thus address the effectiveness of different coping strategies in times of crisis.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Italian natives relied on telephone communication as a coping mechanism more than the other two groups. While staying in touch with family and friends through phone and other media use has been correlated with life satisfaction during the first semi-lockdown in Switzerland (Dones et al, 2022 ), studies found that non-personal communication does not substitute face-to-face interactions and it is not a protective strategy against loneliness among older adults (Pan et al, 2021 ; König and Isengard, 2023 ). Further research should thus address the effectiveness of different coping strategies in times of crisis.…”
Section: Discussionmentioning
confidence: 99%